KEYBOARD BRAILLE DENGAN OUTPUT SUARA SEBAGAI ALAT PEMBELAJARAN UNTUK PENYANDANG TUNANETRA - Nanda, Ardhian Satrio Adi; Anisa, Marselia; Mulatsih, Winahyu Tri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Sense of sight is one of the vital resources for humans. It is normal if noted that most of the information were obtained from the human senses of sight, while the rest come from other senses. Currently the introduction of Braille learning system blind patients still has shortcomings. One of them is when learning takes the role of the teacher is not physically blind to introduce forms of Braille. A teacher should show you exactly what motive and what letters are being touched by people with visual impairments. Of course this greatly affects the speed of visually impaired people to learn Braille, because blind people cannot do on their own learning. The sound system is applied to the keyboard can replace the role of the instructor, both in teaching and in the training process. All data processing are done by the microcontroller. So that the data can be converted into sound through the power amplifier.